ANALISIS BIBLIOMETRIK TERHADAP RISET ADVERSITY QUOTIENT SEBAGAI DISPOSISI MATEMATIS DI GOOGLE SCOLAR MENGGUNAKAN VOSVIEWER - Arif Nurhidayat (Sekolah Tinggi Pariwisata Mataram, 2023)
This bibliometric analysis is based on the mapping of adversity quotient research as a mathematical disposition based on data on Google Scholar. This study aims to determine the level of development of scientific research in the period 2018-2021. Data collection of 500 data was carried out using the Publish or Perish (PoP) application and mapping with vosviewer. Research data is based on the analysis of the year of publication, name and productivity. The results of the study show an increase in scientific publications in 2019 as many as 122 publications and a decrease in scientific publications in 2020-2021. Semarang State University with the journal.uness.ac.id site is the publisher with the most publications, namely 24 publications. The author with the highest level of scientific publication productivity is Effendi with a total of 6 scientific publications and has close research relationships with several researchers. The research theme that is most closely related to the adversity quotient is the student's problem-solving ability. Meanwhile, the rare theme with adversity quotient is Problem Based Learning (PBL).